Value Added Tax Restitution Process in an Effort to Protect the Rights of Corporate Taxpayers at Massaniga & Rekan Tax Consultant Office - Muhammad Adil; Alfarah Firdamayanti; Muhammad Khaedar Sahib (Jurnal Riset Perpajakan: Amnesty, 2023)
Tax restitution is an application for the return of tax overpayments made by taxpayers to the state. This tax overpayment is actually a basic right for taxpayers which otherwise becomes an obligation of the tax authority The purpose of this research is to find out the value-added tax restitution process in an effort to protect the rights of corporate taxpayers at the Massaniga & Rekan Tax Consultant Office. The research object of this Final Project is "The Value Added Tax Restitution Process in an Effort to Protect Corporate Taxpayer Rights at the Massaniga & Rekan Tax Consultant Office". The type of research conducted with an applied skinative approach. The data collection technique used is to use the Interview, Documentation and Observation methods. The results of this study indicate that the value-added tax restitution process carried out by the Massaniga & Rekan tax consultant office has been carried out with applicable rules and implemented to fulfil the rights of corporate taxpayers.